1994
DOI: 10.1002/j.1460-2075.1994.tb06880.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human papillomavirus E2 protein: evidence of trans-activation and trans-repression in cervical keratinocytes.

Abstract: The major regulator of papillomavirus transcription is encoded by the viral E2 gene. The E2 gene has been well characterized in bovine papillomavirus (BPV) where it encodes at least three different polypeptides which differentially affect viral gene expression. In human papillomaviruses (HPVs) the E2 gene product is much less well characterized. In this study we have analysed the mechanism of action of the HPV‐16, HPV‐18 and BPV‐1 E2 proteins in cervical keratinocytes. We show that the full length HPV E2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
151
1
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 37 publications
9
151
1
10
Order By: Relevance
“…Our binding data suggest that the hE2 protein might positively and negatively regulate transcription of its own gene at low and high E2 concentrations, respectively. This hypothesis is consistent with the results of previous studies which have shown that although hE2 activates transcription from the P97 promoter, increased expression of the hE2 protein results in transcriptional repression (18). Similar concentration-dependent effects of HPV 8 E2 have been observed at the HPV 8 late gene promoter (30).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our binding data suggest that the hE2 protein might positively and negatively regulate transcription of its own gene at low and high E2 concentrations, respectively. This hypothesis is consistent with the results of previous studies which have shown that although hE2 activates transcription from the P97 promoter, increased expression of the hE2 protein results in transcriptional repression (18). Similar concentration-dependent effects of HPV 8 E2 have been observed at the HPV 8 late gene promoter (30).…”
Section: Discussionsupporting
confidence: 93%
“…For example, the hE2 protein has been shown to activate transcription from the HPV 16 P97 promoter whereas, under exactly the same conditions, the bE2 protein has been shown to repress P97 promoter activity (18). Our results highlight a further difference between these proteins; in comparison to bE2, the hE2 protein recognizes an extended binding site.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The E2 open reading frame (ORF) encodes at least two or three different proteins which all act as transcription factors and regulate viral transcription (Cripe et al 1987;Baker et al 1987;Bouvard et al 1994). The E2 proteins bind to the E1 and stimulate viral DNA …”
Section: E1 and E2 Proteinsmentioning
confidence: 99%
“…This was left for 5 h prior to removal of the transfection solution disruption of the HPV-16 E2 gene in cervical tumours and the transcriptional repression of the URR detected in initial studies with HPV-16 E2, a model that emerged was that disruption of the E2 gene removes a major negative regulatory influence on the HPV-16 URR (for reviews see Ham et al, 1991 ;McBride et al, 1991). However, more recent studies have suggested that the major function of the E2 protein is as a transactivator of the HPV-16 URR (Bouvard et al, 1994 ;Ushikai et al, 1994), which does not provide an easy explanation for the role of the disruption of the E2 reading frame detected in most cervical tumours.…”
mentioning
confidence: 99%